How incidental and intentional news exposure in social media relate to political knowledge and voting intentions - Dreston, Jana H.; Neubaum, German (Frontiers in Psychology, 2023)
Background Citizens are expected to make informed voting decisions. Theoretical approaches suggest that people are most likely to acquire their political knowledge through media. As more people turn to social media as a source of news, the political knowledge gains from using these technologies are called into question. Previous research has shown that rather than increasing objective political knowledge, the use of social media for news only increases people’s metacognitive sense of being knowledgeable (subjective knowledge), which in turn increases their political participation. However, it remains to be understood which particular forms of social media use, e.g., incidental or intentional news exposure, are related to which dimension of political knowledge. The present work examines (a) the extent to which different motivational forms of social media news consumption foster subjective knowledge, and (b) whether this metacognition is related not only to political participation as a broad concept, but also to specific democratic outcomes such as voting intentions. Methods and results Results from a pre-registered, pre-election survey (N = 1,223) of social media users show that intentional news seeking, but not incidental news exposure on social media, is directly related to increased subjective knowledge. Subjective knowledge appears to explain the relationship between social media news use and voting. Discussion By showing that incidental and intentional social media news use affect subjective knowledge differently, this study provides preliminary and nuanced insights into the ultimate role that social media technologies can play in democratic processes.